Hälsofrämjande arbetsplatser : En undersökning av den psykosociala arbetsmiljön och det hälsofrämjande arbetet inom Luleå kommun. - Enqvist, Elin (2015)
Increasing numbers of sick leave and lowering numbers of health made the municipalityof Luleå to start a project called Health promoting workplaces. The project aims to improve employee health and well-being, by focusing on health promotion and wellness activities. The aim of this thesis is to investigate the psychosocial work environment within a department of the municipality and to identify how the municipality on the basis of this can work with, and create engagement in, health promotion in the workplace among the employees. This thesis is based on Karasek and Theorell’s (1979) Demand-Controll-Support model, Siegrist’s (1996) Effort-Reward Imbalance model and the Sense of Coherence model by Antonovsky (1987/1991). The research questions are: How do the employees experience the psychosocial work environment? How do the employees experience the work of health promotion and how can engagement in health promotion be created among the employees? Ten employees within one unit of the municipality participated in semi-structured interviews, that have been analyzed with a theory based thematic analysis. The results show that employees perceived shortcomings in the organizational and structural factors, which affect their well-being and psychosocial work environment. These factors were hierarchical structures, unclear work processes and a lack of communication and participation. The results also show, that the employees have little knowledge of health promotion in general and workplace health promotion in particular. Finally, the results show that health promotion, the psychosocial work environment and the unit's organizational structure were so closely linked that an improvement of the organizational and structural factors would be a major health promotion activity leading to a better psychosocial working environment. Validerat; 20150624 (global_studentproject_submitter)